Red blood cell alloimmunization in Iran: A Comprehensive review of the literature - Maryam Sadat Hosseini (Asian Journal of Transfusion Science, 2020)
Background: Alloimmunization is an immune response against foreign antigens which introduced into the body through transfusion, pregnancy, or transplantation. This phenomenon is a big challenge in patients, which require regular transfusions. In the current study, we tried to have a comprehensive review on the status of alloimmunization in Iran. For this purpose, we searched for papers investigating alloimmunization in transfusion-dependent patients and also in patients with no regular transfusions who are candidate for surgery or who need blood. Methods: We searched PubMed, Google Scholar, SID, and MAGIRAN databases using the following keywords: “blood transfusion,” “alloimmunization,” “alloantibodies,” “irregular antibodies,” “red cell antibodies,” and “Iran.” No limitation for the date of publication and language of the papers was defined. All the identified records were then screened for the relevance and duplication. Results: A total of 22 papers were included in this study. All of the studies were conducted from 1999 to 2016 and providing alloimmunization data from different cities all over of Iran. In general, the results showed that the most prevalent alloantibodies are anti-Kell (anti-K antigen) and anti-Rh system, mainly anti-E, anti-D, anti-C, and anti-c. Conclusion: Anti-Kell and anti-Rh antibodies are the most prevalent antibodies responsible for alloimmunization in Iranian population.